The effect of combination of hemofilter, pre- and intraoperative methylprednisolone administration on systemic inflammatory response syndrome (SIRS) post open heart surgery - . Supomo; Teguh Aryandono; Marsetyawan Soesatyo; Paulus Sudiharto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2017)
Systemic inflammatory response syndrome (SIRS) occurs in almost all patients whom undergo open heart surgery causes the increase its morbidity and mortality. The effect of pre- and intraoperative methylprednisolone administration combined with hemofilter application in cardiopulmonary bypass machine in the reduction of SIRS incidence remains controversial. This study aimed to evaluate the effect pre- and intraoperative methylprednisolone administration combined with hemofilter on SIRS incidence after open heart surgery. This was an experimental study using prospective randomized open-blinded evaluation (PROBE) design. Ninety-five patients from Dr. Sardjito General Hospital, Yogyakarta, and Dr. Cipto Mangunkusumo General Hospital, Jakarta, who had open heart surgery within the period of December 2011 to May 2012 were enrolled in this study. The patients were randomly allocated into two groups i.e. Group A (48 patients) received pre-; intra-; and postoperative methylprednisolone (15; 5 and 5 mg/kg BW, respectively) and hemofilter and Group B (47 patients) just received intra- and postoperative methylprednisolone (15 and 5 mg/kg BW). The SIRS incidence was evaluated in 3; 24; 48 and 72 hours post surgery. This study showed that the SIRS incidence in Group B at 3 (OR= 0.12; 95%CI=0.03-0.39; p< 0.001) and 24 (OR= 0.38; 95%CI=0.14-0.996; p< 0.031) hours postoperative were significantly higher than that in Group A. In conclusion, pre- and intraoperative methylprednisolone administration combined hemofilter significantly decrease the SIRS incidence post open heart surgery.